Bioactivity-guided Isolation of Phytoconstituents from Saraca asoca Seeds for Anti-asthmatic Potential - Rathod, Chandrakant Prabhu; Ghante, Mahavir (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: It is interesting to consider biologically active substances derived from natural sources as potential novel medications for infectious disorders. Saraca asoca is an indigenous medicinal plant with lots of traditional importance belonging to the family Caesalpinaceae. As these plants have been ethno-pharmacologically claimed for the treatment of respiratory system-related disorders such as asthma, and cough, in addition, to treating inflammatory conditions. The anti-asthmatic activity is not supported by scientific research on Saraca asoca and no data is available for the anti-asthmatic chemical constituent of Saraca asoca seeds. In the present study, the scientific evidence-based anti-asthmatic compound was isolated from methanol fractions of crude extract of Saraca asoca seeds. The current evaluation attempted to assess the antiasthmatic result of repeatedly achieving Saraca asoca seeds extracts using milk-induced leucocytosis as well as eosinophilia in mice. Results from this study suggested that methanolic extracts of SA were most active and further subjected to column chromatography to isolate phytoconstituents. Results: The methanol fraction was determined to be mainly composed of 2-(3,4-dihydroxy phenyl)-3,5,7-dihydroxy-4H-1-benzopyran-4-one. Isolated phytoconstituents were found to exhibit % DPPH scavenging, mast cell stabilization and bronchorelaxent activity in a concentration-dependent manner. Conclusion: These results show the methanol extract of Saraca asoca seeds shows a potential natural ingredient for the treatment of anti-asthmatic activity, which is due to bioactive compounds such as Quercetin.
Keywords: Anti-asthmatic; Quercetin; Milk-induced leukocytosis; Eosinophilia